SIFAT MEKANIS GELAGAR KOTAK PERCOBAAN UNTUK KAYU KONSTRUKSI - Marolop Sinaga; Sadan Widarmana; Surjone Surjokusumo; A A Mattjik (Jurnal Penelitian Hasil Hutan, 1989)
Experimental    laminated   box  beam  were  constructed    for  their  mechanical  properties  test.  The pile  component  of box  beam  was prepared  consisting  of  solid  wood   as upperside  and  downside   flange  and plywood  or particleboard   as left and  right   web.   The  dimension   of  box  beam  is  9.1  cm  x  20 cm x 244  cm where  the dimension   of solid wood are 5.5 cm x3.5   cm  x 244  cm  and the dimensions   of plywood  and particleboard   are 1.8 cm  x 20 cm x 244  cm. All components   were  onnected   by glue,  nail and  combination    of  both.  The  strength   of  box  beam is based on the static  bending  test especially its  modulus  of elasticity  (MOE) and  modulus  of rupture  (MOR)  by Baldwin  universal testing  machine  with ASTM  method.The results  show  that  the  experimental     box  beam produced   had adequate  MOE and MOR  for construction   purpose. The  nail   and  nail-glue   combination    to  connect  plywood  and particleboard   components    with  solid  wood  give  high  value of  MOE and  MOR  of  box  beam.